2019
DOI: 10.1002/ijc.32751
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of serum hyaluronan and propeptide of type III collagen in patients with pancreatic cancer

Abstract: Hyaluronan (HA) and collagen are highly expressed in pancreatic cancer (PC) stroma. HA and collagen accumulation increase tumor interstitial fluid pressure, compromising blood flow and drug penetration. The aim of this biomarker study was to determine the clinical utility of serum HA and the propeptide of type III collagen (PRO‐C3) in patients with PC. A cohort from the Danish BIOPAC study (NCT03311776) including patients with histologically confirmed pancreatic ductal adenocarcinoma (n = 809), ampullary carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…The most dominant proteins in the ECM are the collagens, of which there are 28 different types [7]. Our research group has previously demonstrated that collagens and other ECM proteins can be valuable as non-invasive biomarker tools in different cancer forms [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The most dominant proteins in the ECM are the collagens, of which there are 28 different types [7]. Our research group has previously demonstrated that collagens and other ECM proteins can be valuable as non-invasive biomarker tools in different cancer forms [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The migration of stem-cells according to LMW-HA gradient has been documented [98][99][100][101]. An increase in LMW-HA levels may occur in case of non-alcoholic steatohepatitis complicated with fibrosis [102,103] or of pancreatic cancer [104]. Hyaluronan content of the pancreas governs tissue stiffness and pancreatic islet inflammation [105].…”
Section: Nlr Lmw-ha Fatty Pancreasmentioning
confidence: 99%
“…ECM neo-peptides are increasingly investigated as potential predictive and prognostic biomarkers. For example, C3M and PRO-C3 have shown prognostic and predictive value in metastatic breast cancer and pancreas cancer [28][29][30]. Furthermore, a high ratio of type III collagen degradation to formation (C3M/PRO-C3) at baseline predicts overall survival (OS) in patients with metastatic melanoma and advanced pancreas cancer [23,30].…”
Section: Introductionmentioning
confidence: 99%